Bali Cattle in The Breeding Stock Areas and Their Future Development - Talib, Chalid (Indonesian Animal Sciences Society, 2002)
Bali cattle is one of Indonesian native breed of cattle distributed in almost all Indonesian provinces under small holder rearing system. The breed is easily adapted within many variations of tropical environment in Indonesia. Although there are a big differences of the production performance between places but the reproduction performances reported are always good. The Bali cattle resources in the country are Bali, South Sulawesi, East and West Nusa Tenggara (NTT and NTB). Based on the production performance, Bali cattle in Bali are the best Bali cattle in Indonesian and in population, South Sulawesi is province having the highest population of the cattle. All of Bali cattle in the resource areas have a high prolific with a good calving rate but NTT shows the highest number of calf mortality and Bali is the lowest. Except in Bali, Bali heifers perform a decline adult body weight that caused by no genetik improvement program and less of supported environment. All of the phenomenons are as as a guidance for a higghly adaptation ability of the breed. In addition, introducing a new blood with highly genetic potential together with the improvement in feeding and management should be conducted. Â Key words: Bali cattle, breeding stock, production and development